Recent technical advances in radiofrequency ablations for hepatocellular carcinoma - Dong Ho Lee (Society of Gastrointestinal Intervention, 2021)
Radiofrequency ablation (RFA) has regarded as a curative treatment method for early stage hepatocellular carcinoma (HCC), providing comparable overall survival to surgical resection. However, lack of ideal guiding modality for RFA procedure and higher rate of local tumor progression (LTP) after treatment than surgical resection have been important limitations. To overcome the current limitations of RFA, the fusion imaging between real-time ultrasound and reference computed tomography/magnetic resonance images has been introduced. The fusion imaging could improve the feasibility of RFA for HCC by helping the accurate identification of target HCC, especially for invisible small HCC. In addition, RFA using multiple electrodes with multi-channel generator and various energy delivery modes could improve the therapeutic efficacy, by creating larger ablation volume than RFA using a single electrode. RFA using multiple electrodes can allow no touch ablation technique, which might have a potential to reduce LTP. In this review, these recently introduced ablation techniques will be discussed with the results of both animal and clinical studies.